Implementasi Model Project Based Learning Menggunakan Mind Map terhadap Keterampilan 4C Geografi Siswa Kelas X Fase E SMAN 15 Padang - Amri, Yola Nuraini; Anwar, Syafri; Aliman, Muhammad (Lembaga Yasin AlSys, 2024)
Geography, as a discipline that studies the interaction between humans and the environment, as well as physical phenomena on Earth, plays an important role in developing 4C skills (Communication, Collaboration, Critical Thinking, and Creativity). However, many students still face challenges in applying 4C skills in geography learning. These challenges include a lack of student participation, as seen from their minimal involvement in class discussions, which hinders the development of communication and collaboration skills. This issue is often caused by low self-confidence or insufficient understanding of the material. Additionally, students frequently struggle with critical thinking, particularly in identifying and analyzing complex geographical problems. The method used in this research is descriptive qualitative, with the subjects selected using purposive sampling, resulting in a sample of Class X Phase E 8. Data collection was carried out using assessment rubrics in terms of attitudes, knowledge, and skills to evaluate student activities in creating Mind Maps. The results of this study show that the assessment of Mind Mapping, using the Project-Based Learning model, yielded an overall average score of 81.72, categorized as good, and positively impacted the development of students' 4C skills. Students demonstrated creativity (C6) by creating Mind Maps, which reflect their ability to think critically and creatively, core aspects of Higher Order Thinking Skills (HOTs). Furthermore, they showed improved communication and collaboration abilities in learning, thus achieving the 4C skills.